An Empirical Study on Indonesian English-Curriculum Changes: Opportunities and Constraints in an Underdeveloped Region - Agus Riadi (Indonesian TESOL Journal, 2019)
Ever since Indonesia adopted English as its foreign language in 1945 to be taught in schools, some changes have been made to achieve the national goal of learning the language. These changes were made following the teaching methodologies evolution around the world and later implied in the Indonesian English-curriculum. As the consequence of the implementation, the executor of this curriculum – teachers, in this regard – had to undergo some adjustments regardless of in which region they were teaching. The disparity of the curriculum properties (teacher training, textbooks, etc.) distribution was quite evident in the majority of areas in Indonesia. Therefore, this article examines several opportunities and constraints aimed to provide better insights from the rural-area teachers concerning the curriculum implementation. This research used historical and documentary research in the context of literature on curriculum and teachers’ perception towards some curriculum renewal. The article concludes that despite having a number of changes, the stakeholder appears to fail in addressing the primary need of and providing some adequate assistance for the teachers in underdeveloped regions in readjusting to the change, resulting in the disproportion and disparity compared to those who teach in developed cities.